THE INDUSTRIAL DEVELOPMENT OF PT. PHILLIPS SEAFOOD INDONESIA PASURUAN TO FULFILL BASIC MATERIAL OF CRAB (Portunus pelagicus) - Anindya Feri Anggraini; Mimit Primyastanto; Tiwi Nurjannati Utami (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
The aims of this research are to understand and analize profile, performance, and strategy usage of SWOT analysis (strength, weakness, opportunity, threat) of PT. Phillips Seafoods Indonesia Pasuruan to fulfill basic material of crab. The data are collected by observation and interview. The methods to analyze data are by descriptive qualitative and descriptive quantitative. The result of this research is the multinational firm that walk straight into fishery which is crab can as the primary product. Analyzing of performance of firm in technical aspect is start from receiving to stuffing/ loading process; planning, organizing, moving, and supervising are included management aspect; in short-term financial aspect, the amount of capital Rp 7.957.362.500,- has capital gains about Rp 3.376.255.864,- in month; in social-economic aspect, this firm has some CSR progam; in environment aspect, this firm has UKL and UPL; in law aspect, this firm has the license and right certification; and the marketing aspect, its distribution strategy is to export its product to USA, Europe, and Australia with the fixed price Rp 122.808,- per can. The descriptions above are able to said that PT. Phillips Seafood Indonesia Pasuruan is eliglible and capable of developing. The SWOT analysis indicate that the firm is located in quadrant I, furthermore the usage strategy is proper SO strategy (strengths, oportunity), it means that it can make opportunities by the firm capabilities.Key word: Devekoping strategy, company performance, SWOT analysis